Erythrocyte sedimentation rate and hemoglobin-binding protein in free-living box turtles (Terrapene spp.). - Laura Adamovicz; Sarah J Baker; Ethan Kessler; Marta Kelly; Samantha Johnson; John Winter; Christopher A Phillips; Matthew C Allender (PLoS ONE, 2020)
The acute phase response is a highly conserved reaction to infection, inflammation, trauma, stress, and neoplasia. Acute phase assays are useful for wildlife health assessment, however, they are infrequently utilized in reptiles. This study evaluated erythrocyte sedimentation rate (ESR) in eastern (Terrapene carolina carolina) and ornate box turtles (Terrapene ornata ornata) and hemoglobin-binding protein (HBP) in T. ornata. Erythrocyte sedimentation rate in 90 T. carolina and 105 T. ornata was negatively associated with packed cell volume and was greater in unhealthy turtles (p < 0.05). Female T. ornata had higher ESR values than males (p < 0.05). Measurement of ESR with a microhematocrit tube proportionally overestimated values from a commercial kit (Winpette), though both methods may retain utility with separate reference intervals. Hemoglobin-binding protein concentration in 184 T. ornata was significantly increased in adults and unhealthy turtles (p < 0.05). Erythrocyte sedimentation rate values were similar between seasons and populations, and HBP values were consistent between years, indicating that these analytes may have more stable baseline values than traditional health metrics in reptiles. This study demonstrates that ESR and HBP are promising diagnostics for health assessment in wild box turtles. Incorporating these tests into wild herptile health assessment protocols may support conservation efforts and improve ecosystem health monitoring.